2019
DOI: 10.1136/jech-2018-211309
|View full text |Cite
|
Sign up to set email alerts
|

Long work hours, weekend working and depressive symptoms in men and women: findings from a UK population-based study

Abstract: BackgroundGlobalised and 24/7 business operations have fuelled demands for people to work long hours and weekends. Research on the mental health effects of these intensive temporal work patterns is sparse, contradictory or has not considered gender differences. Our objective was to examine the relationship between these work patterns and depressive symptoms in a large nationally representative sample of working men and women in the UK.MethodThe current study analysed data from Understanding Society, the UK Hou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
40
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 31 publications
5
40
0
2
Order By: Relevance
“…Furthermore, it is worth mentioning that the contemporary globalized society expects the employee to work almost 24 hours a day, including public holidays (Saturdays and Sundays). As some studies conclude, this requirement has become virtually a social norm leading even to the deterioration of mental health [31]. This phenomenon has also been observed in Poland.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…Furthermore, it is worth mentioning that the contemporary globalized society expects the employee to work almost 24 hours a day, including public holidays (Saturdays and Sundays). As some studies conclude, this requirement has become virtually a social norm leading even to the deterioration of mental health [31]. This phenomenon has also been observed in Poland.…”
Section: Introductionmentioning
confidence: 84%
“…According to the literature, numerous risk factors for the development of occupational stress result from the daily burdens associated with work structure, e.g. work time, number and working conditions [2,31]. According to the Euro Health Consumer Index, Poland is 31st among 36 countries due to the level of professional overwork among doctors [33].…”
Section: Introductionmentioning
confidence: 99%
“…Combining employment with increased childcare, homeschooling and housework may have increased feelings of psychological distress through reduced time for sleep and leisure, and the stress of trying to meet competing demands. Previous work has documented the mental health effects of working non-standard hours (Weston, Zilanawala, Webb, Carvalho, & McMunn, 2019), as well as combining care provision with full-time employment (Lacey, McMunn, & Webb, 2019). A national survey of the UK during lockdown also showed that women's psychological distress rose more than men's during lockdown (Banks & Xu, 2020).…”
mentioning
confidence: 99%
“…On the relational level, male partners have to share the burden of family commitment which would eventually lessen the weight carried among academic mothers as studies have shown that women are more prone to work and family stress when subjected to longer working hours (Michie, 2002;Weston et al, 2019) that might affect the cognitive function (Virtanen et al, 2009). At the institutional level of the academia, a more progressive outlook regarding policy formulation for work-family balancing issues should be crafted (Amer, 2013).…”
Section: Suggestionsmentioning
confidence: 99%